Guns in America - H.W. Wilson Company (Amenia, New York : Grey House Publishing, 2017)
A national debate continues to rage in regard to 2nd Amendment rights in contemporary society. This collection will deal with concerns about domestic violence committed by guns, the ramifications of a widely armed citizenry, the government's failure to pass comprehensive gun legislation, as well as police brutality, strong gun lobbies, open carry laws, home-grown terrorism, the recent rise of fatal shootings of black men by police, and the Orlando massacre. From domestic terrorism to the Black Lives Matter movement articles in this title reflect differences in policy views on the subject in the longstanding debate around gun rights and gun control.--Publisher information.
1. Ideology of guns : -- Firearms in America: personal liberty versus collective responsibility -- Gun debate: is price of an armed America a more dangerous America? / Patrick Jonsson -- Most Americans believe we should have gun regulation / Ann Christiano, Annie Neimand -- Gun research faces roadblocks and a dearth of data / Meghan Rosen -- The Senate voted on 4 popular gun control proposals Monday: here's why none of them passed / Amber Phillips -- The gun fight in Congress / Jelani Cobb -- As Congress returns, Democrats and Republicans clash over gun control / Josh Siegel -- 2. Searching for balance in gun policy : -- Perspectives on gun policy -- A gun lover's case for gun control: not all of us believe in the right to bear assault weapons / Ron Cooper -- How I got licensed to carry a concealed gun in 32 states by barely trying / Tim Murphy -- It's time to ban guns. Yes, all of them / Phoebe Maltz Bovy -- The gun control "terror gap": what is it-and why hasn't Congress fixed it? / Andrew Gumbel -- Anti-gun hysteria is hazardous to your health / David French -- Four major problems with gun control arguments / Dustin Murphy -- Inside the power of the NRA / Robert Draper -- A criminologist's case against gun control / Jacob Davidson -- 3. A global perspective : -- Guns in the global sphere -- Why America isn't the only country that wants guns for self-defense / Jennifer Carlson -- Why the gun lobby is winning -- US gun policy: global comparisons / Jonathan Masters -- How US gun control compares to the rest of the world / John Donahue -- 4. Trends in the gun debate : -- Trends in the gun debate -- Untangling gun violence from mental illness / Julie Beck -- How racial prejudice helps drive opposition to gun control / Alexandra Filindra -- The home-grown threat -- What public health researchers want you to know about gun control / Ziming Xuan and Sandro Galen -- Blaming gun violence on the mentally ill is easy, but ignorant / Jason Powers -- Fixation on terrorism blinds US to domestic threats to national security / Michael A. Cohen -- How to prevent gun deaths? Where experts and the public agree / Quoctrung Bui and Margot Sanger-Katz -- 5. The future of guns in America : -- Alternative futures in gun policy -- Donald Trump's big gun idea? Literally stolen from Tim Kaine / Brandy Zadrozny -- Gun control advocates find a deep-pocketed ally in big law / Jessica Silver-Greenberg and Ben Protess -- Under Donald Trump, what will happen on guns? / Michele Gorman -- Gun laws and terrorism: an American nightmare / John Cassidy -- Quantifying the social cost of firearms: a new approach to gun control / Timothy M. Smith.
Includes bibliographical references (pages 175-178) and index.
Keywords: Gun control -- United States; Firearms -- Government policy -- United States; Firearms ownership -- United States; Firearms -- United States; Violent crimes -- United States; Firearms; Firearms -- Government policy; Firearms ownership; Gun control; Violent crimes